Balancing the Oral Redox State: Endogenous and Exogenous Sources of Reactive Oxygen Species and the Antioxidant Role of Lamiaceae and Asteraceae - Caterina Nela Dumitru; Lupoae Mariana; Cristian Constantin Budacu; Gabriela Mitea; Marius Daniel Radu; Alina Oana Dumitru; Andreea Lupoae; Alin Tatu; Gabi Topor (Dentistry Journal)
Background/Objectives: Oral health is a complex concept involving physical, psychological, emotional, and social components. A key factor in maintaining oral tissue integrity is redox balance, which is disrupted by oxidative stress (OS) through an imbalance between reactive oxygen species (ROS) and antioxidant defenses. This study examines the contribution of endogenous and exogenous sources to OS and explores the therapeutic potential of medicinal plants from the Asteraceae and Lamiaceae families in restoring redox homeostasis and improving oral health. Methods: A literature review was conducted, analyzing the role of OS in oral diseases and the antioxidant mechanisms of selected Asteraceae species. Special attention was given to their phytochemical contents—polyphenols, flavonoids, and essential oils—and their biological relevance to oral health. Results: OS plays a critical role in the onset and progression of oral conditions such as caries, periodontitis, gingivitis, aphthous ulcers, abscesses, precancerous lesions, and oral cancers. ROS and reactive nitrogen species (RNS) cause inflammation, tissue breakdown, and salivary gland dysfunction. Asteraceae plants like Matricaria chamomilla, Calendula officinalis, Cichorium intybus, Taraxacum officinale, Arctium lappa, Achillea millefolium, and Solidago virgaurea demonstrate notable antioxidant, anti-inflammatory, and antimicrobial properties that help counteract OS and support oral homeostasis. Conclusions: Asteraceae and Lamiaceae species show high therapeutic potential in addressing OS-related oral disorders. Their bioactive compounds aid in restoring redox balance and protecting oral tissues. These findings support the integration of phytotherapeutic agents into oral healthcare and call for further clinical validation of plant-based strategies for disease prevention and management.